A Review of Income Smoothing through Company Size, Profitability, and Managerial Ownership - Munasiron Miftah; Fanny Dwi Oktaviani; Yudi Nur Supriadi (Garuda Prestasi Nusantara Consulting, 2023)
This study was conducted to test empirically the effect of firm size, profitability, and managerial ownership on income smoothing with firm age and leverage as control variables. Income smoothing is proxied using the Eckel index. This research is a quantitative research and the objects in this research are manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. Selection of sample criteria was carried out by purposive sampling technique with predetermined criteria and obtained data of 282 samples obtained from 94 companies. Testing the hypothesis in this study used multiple linear regression analysis with the help of STATA software version 16. The results of this study indicate that 1) company size has no effect on income smoothing; 2) profitability has no effect on income smoothing; and 3) managerial ownership has no effect on income smoothing. Keywords: income smoothing; Company Size; Profitability; Managerial ownership.